Investigating the factors of committing crime by foreign workers using fuzzy techniques / Norwaziah Mahmud ... [et al.] - Mahmud, Norwaziah; Maslin, Nur Aisyah; Jamaluddin, Siti Hafawati; Muhammat Pazil, Nur Syuhada (UiTM Cawangan Perlis, 2022)
Criminal activities have a huge detrimental impact on society and the country. Foreign workers are among the contributors to the crime rate in Malaysia. Crime rate will not decrease if the factors that influence foreign workers to commit crimes remain unclear and unexplored. Many factors are affecting the foreign workers to commit crime. This research aims to determine the ranking for the factors of committing crimes by foreign workers. The Fuzzy Technique for Order Preference with Similarity to Ideal Solution (TOPSIS) was applied to rank the factors. The alternative of this research is the factors of committing crimes by foreign workers, which are lack of facilities, poverty, wage discrimination, fraud by employment agents, alcohol and drug abuse, and poor education level. The criteria chosen are ex-criminal, desperate individual, legal immigrant and illegal immigrant. Three decision-makers which are police officers must assess the factors in this research using linguistic variables ranging from "very poor" to "very good". The alternatives that would be chosen have the shortest distance to Positive Ideal Solution (PIS) and the farthest distance to Negative Ideal Solution (NIS). Finally, this study demonstrates that the highest ranking for the factors of committing crime by foreign workers is wage discrimination with a closeness coefficient value of 0.5305. The minor contributing factor with a closeness coefficient value of 0.2744 comes from poverty. Many personnel may benefit from the findings of this study. This study provides information about the factors of committing crime most associated with foreign workers, allowing employers to be aware of the risk they come with. This requires them to be more responsive to their employees, such as monitoring employee movement to track their daily activities (e.g., installing security cameras the housing facilities). Besides, employers should fairly deal with their employees and keep the workforce motivated to avoid criminal cases. A future study might broaden the scope of the project by including various sorts of criteria and alternatives.